Regtech as an antitrust enforcement tool. (15th June 2020) - Nicholls, Rob
Abstract: Financial technology (Fintech) has been applied to business models in the financial services sector. Associated with this has been the rise of regulatory technology (Regtech) in that sector. However, the major application of Regtech in financial services is as a tool for regulatory compliance, rather than for regulatory enforcement. This article explores an approach to applying Regtech techniques to antitrust enforcement. It does this by applying those techniques to the detection of resale price maintenance (vertical price fixing). The exploration is limited to pricing on e-commerce platforms such as AliExpress, eBay, and Amazon Marketplace. The Regtech application is effected by presenting the literature and cases on resale price maintenance and the application of the law in Australia, the US, and the EU. The article examines the application of machine learning in the Regtech environment and the ways in which application programming interfaces could be used. The article proposes approaches to machine learning solutions for the detection of potentially infringing resale price maintenance conduct. It also presents the basis of an algorithm for detecting that conduct.